RELIGION AND THE PROBLEM OF DEATH - Breckenridge, James (Journal of Dharma, 1979)
The problem of confronting death is found. in all the major world religions. In this paper, however, I shall limit my consideration of this problem to Zen Buddhism and Christianity. My reasons for doing this are twofold: First, in recent years a number of publications have maintained that Zen and Christianity provide an especially meaningful context for interreligious dialogue.’ I hope that at least in a small way this paper will lend some support to that thesis. Second, the importance of meeting death with an attitude of composure is a theme that appears frequently in Zen and Christian writings.